2009
DOI: 10.1111/j.1750-3841.2009.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Artemisia Capillaris Induces Apoptosis in KB Cells via Mitochondrial Stress and Caspase Activation Mediated by MAPK‐Stimulated Signaling Pathway

Abstract: Artemisia capillaris has been used in traditional Korean medicine for its variety of pharmacological activities. Previous studies have suggested that the essential oil of A. capillaris has chemopreventive potential, even though the mechanism of its action is unclear. This study examined whether or not the essential oil isolated from A. capillaris induces apoptosis in the human oral epidermoid carcinoma cells along with the possible mechanism(s) of the essential oil-mediated cytotoxicity. The essential oil indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…In addition, it has been recently shown that the toxicity of Artemisia annul L. on cultured hepatocarcinoma cells SMMC-7721 is mainly mediated by apoptosis [48]. Essential oils of Artemisia capillaris and Artemisia iwayomogi have been reported to induce apoptosis in KB human oral epidermoid carcinoma cells via mitochondrial stress and caspase activation mediated by MAPK-stimulated signaling pathway [15]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been recently shown that the toxicity of Artemisia annul L. on cultured hepatocarcinoma cells SMMC-7721 is mainly mediated by apoptosis [48]. Essential oils of Artemisia capillaris and Artemisia iwayomogi have been reported to induce apoptosis in KB human oral epidermoid carcinoma cells via mitochondrial stress and caspase activation mediated by MAPK-stimulated signaling pathway [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Essential oils of A. absinthium which contained higher amounts of trans-sabinyl acetate and cis/trans-thujones exhibited more toxicity on brine shrimp (Judzentiene et al, 2012). Moreover, the essential oils of A. capillaris and A. herbaalba are regarded as good candidates for further study, because they showed significant anti-proliferative activity against the human oral cancer and acute lymphoblastic leukaemia (CEM) cell lines respectively (Cha et al, 2009;Tilaoui et al, 2011). Dichloromethane extracts of A. annua exhibited higher cytotoxicity in comparison with methanol extracts against HeLa cancer cells (Efferth et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…EO-induced apoptosis has been also suggested to be involving mitochondrial and MAPKs pathways [23]. Antiapoptotic Bcl-2 protein is downregulated by the action of EOs on the cancer cells [47]. In mouth cancer KB cells, Artemisia lavandulaefolia EO has been shown to decrease Bcl-2 protein level in dose dependent manner [23], which leads to apoptosis in cancer cells that is an important strategy to control cancer development and progression.…”
Section: Mechanism Of Action Of Eosmentioning
confidence: 99%
“…Human leukaemia cell line (HL-60) treated with EO of Cymbopogon flexuosus and its major constituent isointermedeol has been reported to lower NF- κ B which is one of the contributing multiple pathways resulting in apoptosis [58]. EO of Artemisia capillaries leads to NF- κ B-DNA binding activation at the concentration above 0.5  μ L/mL, leading to apoptosis in the mouth cancer KB cells [47]. …”
Section: Mechanism Of Action Of Eosmentioning
confidence: 99%